Incidence, mortality and survival of bladder neoplasms in the Czech Republic in the period 1977-2017: a time trend analysis - Pehalova, L; Krejčí, D; Büchler, T; Janošek, J; Dušek, L (Klinicka onkologie, 2021)
BACKGROUND: Bladder neoplasms represent a significant disease burden in the Czech population. This study aimed to perform a complex time trend analysis of incidence, mortality, and survival of 76,505 patients with bladder neoplasms based on the Czech National Cancer Registry for 1977-2017. MATERIALS AND METHODS: The time trends of incidence and mortality were evaluated using the joinpoint regression. The relative survival and Cox proportional hazards model were used for survival analysis. RESULTS: After 2004, a significant annual decrease by 1.9% in the incidence of malignant tumors of the bladder (C67) was observed, accompanied by a sharp annual increase in the incidence of in situ bladder cancer (D090) by 16.9%. For mortality from malignant tumors of the bladder, a significant decrease by 1.4% annually was detected after 1998. The decline in both incidence and mortality was most pronounced in the below-65 years age group and in patients with a localized stage at dia-gnosis. While a significant decline in both incidence and mortality was observed for the first primary malignant tumors of the bladder, both these measures increased for malignant tumors of the bladder as subsequent primary neoplasms. The five-year relative survival of patients with malignant tumors of the bladder increased from 52.1% in 1990-1993 to 62.3% in 2013-2017. However, comparing the periods 2003-2007 and 2013-2017, a decrease has been observed. CONCLUSION: The decrease in the incidence and survival of malignant tumors of the bladder in the recent period is in particular caused by improved detection of in situ bladder cancer and classification changes. Other reasons for the decreasing survival include the increasing age at dia-gnosis, the growing number of subsequent primary neoplasms, and the increasing proportion of smokers among patients.
Keywords: Registries; time trends; Czech National Cancer Registry; Humans; in situ bladder cancer; lidé středního věku; registrace; prevalence; Female; Aged; senioři; lidé; subsequent primary neoplasms; survival; malignant tumors of the bladder; ženské pohlaví; mortality; Male; nádory močového měchýře; Middle Aged; incidence; Incidence; Czech Republic; Prevalence; Česká republika; mužské pohlaví; Urinary Bladder Neoplasms